Avenue (rue) Coloniale. Issue 2 (3rd July 2019) - Morgan, Ceri
Abstract : This prose-poem is part of a larger critical-creative project on Montreal, which mixes memoir, feminist theory and literature. A key intertext is Nicole Brossard's French Kiss, a celebration of language and desire. In Brossard's counter-cultural novel, Marielle/Elle drives across Montreal from a French-speaking east side to English-speaking west side and back again. At the same time—a time outside patriarchal time—a francophone and anglophone woman engage in a lengthy kiss which is projected across urban space. Other moments see the women hang out with Marielle and two male friends, exploring and enjoying the pleasures of the city. My prose-poem is a tribute to Brossard's novel, Montreal, and the feminist writer, Martine Delvaux, who lives in, and has written about, a neighbourhood featured in French Kiss .